Keeping Ebola at bay: public authority and ceremonial competence in rural Sierra Leone. Issue 1 (March 2022) - Kamara, Foday; Mokuwa, Gelejimah Alfred; Richards, Paul
Abstract: Ebola Virus Disease struck Sierra Leone in May 2014. An international response was instrumental in ending the epidemic by December 2015 and has been extensively documented. Less attention has been paid to local responses. Here, we focus on a case in which there was no infection despite high infection in neighbouring areas. This brings into focus the role of customary public authority in implementing successful controls. We pay particular attention to the activities of a chiefdom Ebola Task force committee chaired by the Paramount Chief. Meetings were characterised by protocol and ceremony, but 'face time' served to reinforce, in ritual terms, important messages about quarantine and social distancing. The committee's pronouncements had illocutionary force. Local volunteers translated this ceremonial message into practical action to block imported cases. The analysis of ceremonial competence, we conclude, opens a window into how public authority addresses developmental shocks in Africa.